2001
DOI: 10.1103/physrevb.63.245205
|View full text |Cite
|
Sign up to set email alerts
|

First-principles studies of beryllium doping of GaN

Abstract: The structural and electronic properties of beryllium substitutional acceptors and interstitial donors in GaN are investigated using first-principles calculations based on pseudopotentials and density-functional theory. In p-type GaN, Be interstitials, which act as donors, have formation energies comparable to that of substitutional Be on the Ga site, which is an acceptor. In thermodynamic equilibrium, incorporation of Be interstitials will therefore result in severe compensation. To investigate the kinetics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
5
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(104 citation statements)
references
References 34 publications
9
89
5
1
Order By: Relevance
“…Beryllium appears to be a better acceptor than Mg in GaN for two reasons [4,5]. First, the formation energy of Be acceptors is slightly lower than that of Mg, indicating higher solubility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beryllium appears to be a better acceptor than Mg in GaN for two reasons [4,5]. First, the formation energy of Be acceptors is slightly lower than that of Mg, indicating higher solubility.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that the most stable configuration for the Be Ga -H complex has H sitting in a bond-center (BC) position in a Be Ga -N bond along the c axis [5]. The relaxed structure of the Be Ga -H complex defect in GaN is shown in Fig 2(a).…”
Section: Local Vibration Modes Of Be Ga -H Complex Defect In Ganmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Recently it has been proposed that Be i atoms migrate to Be Ga and form (Be-Be) Ga donors. 20 The presence of these defects would also explain the failure to achieve p-type electrical activity in GaN doped with Be.…”
Section: Ga and 71mentioning
confidence: 99%
“…The latter was reported to ensure the highest intentional free carrier concentration of 8 Â 10 18 cm À3 [6]. The p-type doping in HVPE GaN growth can be achieved by using Zn [7], Cd [8], Be [9], or Mg [10], [11]. Today Mg doping, shown to be relatively more efficient, is mostly used by adding pure metal or powder Mg in a separate boat or mixed with Ga metal and exposed to the HCl.…”
Section: A Hydride Vapor Phase Epitaxymentioning
confidence: 99%